SYSTEMATIC LITERATURE REVIEW : PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING DALAM MENINGKATKAN KETRAMPILAN PRAKTIK INDUSTRI SISWA TINGKAT KEJURUAN - Amalia Miranti (ADIBA : JOURNAL OF EDUCATION, 2024)
Apart from the fact that the vocational preparation prepared by each vocational school is not optimal, because students do not yet have insight into industrial practice in the field, the impact of direct practical learning in industry is still very low. Therefore, teachers are expected to provide preparatory training to improve students' abilities and provide industrial training as well as additional training with preparatory training. The purpose of this research is to find out that the application of the Discovery Learning Learning Model can improve the skills of vocational level students. The method used in this research is the SLR (Systematic Literature Review) method. . In this Systematic Literature Review research, there are 10 journals to be studied in more depth. The research results show that. 1) Application of the Discovery Learning Learning Model can improve vocational level students' industrial practical skills. 2) Before students enter the field, students can be given the theories that will exist later and also how to solve problems if there are problems using discovery learning. 3) By using this discovery learning model, learning in the classroom can be carried out systematically and in a fun and enjoyable learning atmosphere, students are required to be more active in ongoing learning activities, can improve students' analytical skills in solving problems, have a high sense of self-confidence so that it can reduce fear and doubt in students, and also ensure that interaction and cooperation between students and other students can run well.